1966
DOI: 10.1246/bcsj.39.1683
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Hydrogen Exchange of Aniline on Supported Metal Catalysts

Abstract: The hydrogen exchange reaction of aniline with deuterium was investigated on supported nickel, cobalt and platinum. The following results were obtained: 1) At 150°C, the hydrogen of the amino group of aniline exchanges at a higher velocity than the hydrogen attached to the benzene ring. At temperatures as high as 300°C, the hydrogen exchange in the benzene ring increases further. 2) The suggested hydrogenation mechanism obtained from the results of the exchange reaction can not be correlated with that obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…No exchange of the alkyl hydrogens in C 2 H 5 ND 2 , CH 3 ND 2 , and (CH 3 ) 2 ND had been observed by Roberts et al in 1939 over reduced nickel catalyst at 20−195 °C . Hagiwara and Echigoya studied H/D exchange with aniline over Pt and Ni; their results indicate that H atoms in the amino group exchange faster than those at the benzene ring …”
Section: Discussionmentioning
confidence: 91%
“…No exchange of the alkyl hydrogens in C 2 H 5 ND 2 , CH 3 ND 2 , and (CH 3 ) 2 ND had been observed by Roberts et al in 1939 over reduced nickel catalyst at 20−195 °C . Hagiwara and Echigoya studied H/D exchange with aniline over Pt and Ni; their results indicate that H atoms in the amino group exchange faster than those at the benzene ring …”
Section: Discussionmentioning
confidence: 91%
“…H/D exchange of ethylamine on zeolite NaY-supported transition-metal catalysts has been studied using NMR and mass spectrometry, and it was concluded that the main product for a Pt/NaY catalyst is CH 3 CH 2 NHD, which supports our findings for the coadsorption experiment. The preferential H/D exchange of amine over alkyl groups on Pt catalysts has also been observed for diethylamine and aniline . On the other hand, H/D exchange of alkylamines on Ru catalysts has been found to occur at the methylene group …”
Section: Discussionmentioning
confidence: 83%
“…The preferential H/D exchange of amine over alkyl groups on Pt catalysts has also been observed for diethylamine 46 and aniline. 47 On the other hand, H/D exchange of alkylamines on Ru catalysts has been found to occur at the methylene group. 46 5.3.…”
Section: Discussionmentioning
confidence: 99%
“…Further examples of double-bond isomerisation in cyclo-octatetraene derivatives have been examined by n.m.r. spectroscopy.l57 Cyclo-octatetraene reacts with cyanonitrene to give both the 1,Z-and 1,4-adducts ( 157) and (158); it was suggested that these are respectively the products of addition of singlet and triplet cyanonitrene species.158 Dicyclo-octatetraeno[1,2 : 4,5]benzene (159), a potentially aromatic 18n-electron system, has been synthesised 159 by the reaction of 7,8-dimethylene-1,3,5-cyclo-octatriene (137) with 1,Zdehydrocyclo-octatetraene, (159) shows no evidence of aromatic character in the eight-membered rings and the n.m.r. chemical shifts of the nonbenzenoid protons are similar to those of the non-benzenoid protons of benzocyclo-octatetraene.…”
Section: (153)mentioning
confidence: 99%